2018
DOI: 10.31000/bvaj.v1i2.474
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Opini Audit Going Concern Pada Perusahaan Manufaktur Di Bei Tahun 2013-2016

Abstract: The purpose of this study is to examine and analyze the influence of internalfactors such as profitability, liquidity, solvency, cash flow and corporate growth ongoing concern audit opinion. The research design is causality with the unit ofanalysis is the company of the samples taken by purposive sampling technique on thepopulation of manufacturing companies listed on the BEI year 2013-2016. Analyticaltechnique used is logistic. The results showed that simultaneously the independentvariables have an effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Greater operational cash flow suggests the company's healthy financial status since it demonstrates its ability to defend operating capacity while concurrently managing its total debt. The finding of this research is in line with Anita (2017) and Alamsyah (2018), which found that cash flow negatively influences accepting the going concern audit opinion.…”
Section: Opinionssupporting
confidence: 86%
See 2 more Smart Citations
“…Greater operational cash flow suggests the company's healthy financial status since it demonstrates its ability to defend operating capacity while concurrently managing its total debt. The finding of this research is in line with Anita (2017) and Alamsyah (2018), which found that cash flow negatively influences accepting the going concern audit opinion.…”
Section: Opinionssupporting
confidence: 86%
“…A high cash flow ratio shows that a company has enough funds fulfilled its obligations and continues its business in the future (Rahmadia & Sutrisno, 2019). In this research, cash flow is proxied by comparing operating cash flow to the total debt ratio, which refers to the study conducted by Alamsyah (2018).…”
Section: Cash Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous studies that stated that the liquidity ratio significantly affects OAGC (Salawu et al, 2017;Saifudin & Trisnawati, 2016;Putra & Suryandari, 2010;Januarti & Fitrianasari, 2008;Boone et al, 2010). However, this is inconsistent with a previous study, which stated that the liquidity ratio has a significant effect on the provision of OAGC (Alamsyah, 2017;Anita, 2017;Gallizo & Saladrigues, 2016;Lie et al, 2016;Muttaqin & Sudarno, 2012;Özcan, 2016;Pasaribu, 2015;Rafflesia, 2015;Rudkhani & Jabbari, 2013;Sherlita & Puspita, 2012;Suksesi & Lastanti, 2016;Zukriyah, 2012).…”
Section: Liquidity and Going Concern Audit Opinionssupporting
confidence: 60%
“…The results of this study are in line with the previous research, which stated that solvency does not affect providing an audit opinion with a going concern status to the company (Ha et al, 2016;Ibrahim & Raharja, 2014;Januarti & Fitrianasari, 2008;Muhamadiyah, 2013;Muttaqin & Sudarno, 2012;Putra & Suryandari, 2010;Rafflesia, 2015;Sherlita & Puspita, 2012;Suroto & Kusuma, 2017;Wulandari, 2014). However, it does not support the statement that solvency affects the auditor in providing an audit opinion with a going concern status (Özcan, 2016;Rudkhani & Jabbari, 2013;Alamsyah, 2017;Anita, 2017;Lie et al, 2016;Pasaribu, 2015;Saifudin & Trisnawati, 2016).…”
Section: Solvency and Going Concern Audit Opinionsmentioning
confidence: 93%